THE ROLE OF MANAGING THE IMPROVEMENT OF THE TERRITORY IN FORMATION OF IMAGE OF THE MOSCOW CITY - E. Hmelchenko; C. Zaic (Вестник университета)
The article considers the main approaches to building an effective system for the formation of a positive image of the city through the improvement of the territory.